Barriers and opportunities to increase soil organic carbon in vineyards: A case study of extension personnel in France and in the United States - Marie Thiollet-Scholtus; Amélie CM Gaudin; Justine Vanden Heuvel (OENO One)
Increasing soil organic carbon (SOC) in vineyards enhances soil health with associated benefits for climate change resilience and mitigation. However, adoption of SOC-building management practices remains low and hindered by multifaceted barriers. Extension specialists play a crucial role in overcoming adoption challenges by providing tailored advice and training opportunities to growers. This study used semi-structured interviews with extension specialists in warm and cool regions of France and USA to explore context-specific barriers and opportunities for adoption of SOC-building practices. The Multi-Level Perspective framework was implemented to identify SOC-building practices and factors influencing their adoption from niche to mainstream. The practices to increase SOC identified included cover crops, organic fertilisation, and reduced tillage, with regional variations in implementation across climates. Barriers to the adoption of SOC-building practices were centred around costs of implementation, limited knowledge of the long-term impacts of the practices and the complexity of local adaptations of practices to be effective in specific vineyard conditions (e.g., slope, planting density, water availability). Incentives for adoption could include facilitations between grape growers and livestock farmers, targeted research, improved extension programs, and government support through subsidies or restructuring of the supply and value chain both in France and in the USA. A significant gap in extension capacity was identified for cover crop implementation in the USA's warm and cool areas. Research gaps were identified around pruning residue management, the application of arbuscular mycorrhizal fungi, and the integration of grazing animals into winegrape vineyards more in the USA than in France. Expanding applied research and cost-benefit analysis and the long-term impact of these practices is crucial for improving adoption rates of SOC-building practices in the context of climate change.